POTENSI WISATA ALAM HUTAN MANGROVE DI KAWASAN PT. KANDELIA ALAM KABUPATEN KUBU RAYA KALIMANTAN BARAT - Pransiska, Oka; Kartikawati, S M; Roslinda, Emi (Universitas Tanjungpura, 2017)
The mangrove forest is one of the very important natural resources for the forestry and fishery that is closely related to the preservation of aquatic ecosystem. The mangrove forest in PT. Kandelia Alam is 18.130 ha in size. The mangrove forest area has of PT. Kandelia Alam has potential of natural attraction that can be develoved as a tourist area such as the endemic flora and fauna, aquatic biodiversity and many other activities to do in the area. The purpose if this research was to determine the potential of objects that exist in the area of PT. Kandelia Alam. This research was conducted through observation and Accidental sampling in the field and conducted with a descriptive analysis. The potential of the natural attraction found in the area includes mangrove forest ecosystem consisting of fauna, flora, mangrove forest vegetation, aquatic biodiversity, and black hornbill (Anthracoceros malayanus), and the flora are mangrove (Rhizophora apiculata), teruntum (Lumnitzera littorea), belukap (Rhizophora mucronata), and endemic species of kandelia (Kandelia candel), types of vegetation of mangroves, and nypa vegetation, while the natural phenomena are the sun set and the water flow; aquatic biodiversity found there : crab, shrimp, and fish ; the activities that can be done as the tourist potential are boating, photography, wildlife observation, fishing, enjoying views of the sun set, and research. The potential of mangrove forest ecosystem are considered either to be develoved as a natural tourist attraction of mangrove forest in the area of PT. Kandelia Alam by in volving various parties such as the office of tourism, the community, and the WWF (World Wide Fund For Nature) and a good coorperation.Keyword : Attraction nature, Mangrove forest, Potential.